Peran Wanita dalam Islamisasi Jawa abad XV (History Department, Semarang State University and Historian Society of Indonesia, 2011)
Islamization cannot be separated from the role of the people who had been instrumental in spreading Islam. However, the writing of our history is still less in giving ample scope to the role of women in Islamization. This paper briefly tried to raise issues about the status of women in the early Islamization is happening on the island of Java, and how the role of women as part of Islamization. In general, women have a role as a catalyst between the previous culture to culture influenced by aspects of Islam. The role of women as a catalyst because it can facilitate the development of Islam in Java, so that she is regarded as a connecting bridge between the Hindu-Buddhist old culture on the one hand, and the Islamic culture as a new culture on the other hand. The role of women can be seen from his social status, when women have a high social status they have the flexibility to provide access and convenience, as well as strengthening the spread of Islam in Java. Key words: women, Islamization of Java, the cultural catalyst, reinforce